Studi Perbandingan Imunohistokimia NeuN dan NSE untuk Penilaian Neuroprotektif Kombinasi Centella asiatica, Kayu Manis, dan Spirulina pada Cedera Otak Traumatis - Rohadi Rohadi; Bambang Priyanto; Januarman Januarman; Lale Maulin Prihatina (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2025)
Background: Traumatic brain injury (TBI) is a major cause of morbidity and mortality globally, often resulting in cognitive and functional impairment. Effective neuroprotective strategies are needed to mitigate secondary injuries following TBI. This study evaluated the neuroprotective effects of combined Centella asiatica, cinnamon, and spirulina using NeuN and neuron-specific enolase (NSE) immunohistochemical staining in a rat model of TBI. Methods: Ten male Sprague-Dawley rats (200–400 g, 10–12 weeks) were subjected to TBI using the modified Marmarou model and treated orally with a combination extract of Centella asiatica, cinnamon, and spirulina for 10 days. On day 11, brain tissues were collected for histopathological examination and immunohistochemical staining using NeuN and NSE markers to evaluate neurogenesis and neuronal survival. Results: Immunohistochemical analysis revealed a mean positive expression of 71.66% in the NeuN group, indicating increased neuronal survival and neurogenesis, while the NSE group consistently showed 0% positive staining across all samples. The NeuN staining provided a clear depiction of neuronal preservation in the brain tissue, whereas NSE did not demonstrate detectable neurogenesis or neuronal protection in this model. Conclusion: The administration of a combined extract of Centella asiatica, cinnamon, and spirulina demonstrated neuroprotective effects in a rat model of subacute traumatic brain injury, as indicated by increased NeuN immunohistochemical expression, reflecting enhanced neurogenesis and neuronal survival. NeuN staining provided a clearer and more sensitive depiction than NSE, supporting its reliability as an immunohistochemical marker for evaluating neuroprotection and neurogenesis during the subacute phase of TBI in models treated with herbal-based interventions.